ANALISA PENGARUH PROMOSI, INFLUENCER DAN BRAND AMBASSADOR TERHADAP MINAT BELI PRODUK SKINCARE SKINTIFIC DI MEDIA SOSIAL TIKTOK - Albiansyah, Albiansyah; Indah Hanna , Ameylia (Management Research and Business Journal, 2025)
This study aims to analyze the influence of promotions, influencers, and brand ambassadors on purchase intention for Skintific skincare products. This study used a quantitative method, collecting data through a questionnaire distributed to 100 respondents who are Skintific product users. The analysis results using Statistical Product and Service Solutions (SPSS) showed a multiple linear regression coefficient of Y = 7.421 -5.741X1 + 5.931X2 + 0.662X3 and an adjusted R-squared value of 0.729, or 72.9%. The t-test values for X1 = 0.024, X2 = 0.019, and X3 = 0.000. The independent variables in this study were Promotion (X1), Influencer (X2), and Brand Ambassador (X3), while the dependent variable was Purchase Intention (Y). From the results of the t-test analysis with a significance level of 5% shows that Promotion has a significant negative influence on purchasing interest, with a t-count value of -5.759 and a significance of 0.024 (0.024 <0.05), influencers show a significant positive influence on purchasing interest, with a t-count value of 5.996 and a significance of 0.019 (0.019 <0.05),  Brand Ambassador has a significant positive influence on purchasing interest, with a t-count value of 0.650 and a significance of 0.000 (0.000 <0.05). The results of the F test show that simultaneously or simultaneously the promotion variable and brand ambassador have an influence on purchasing interest. With an F-count value of 89.567 with a significance level of 0.000 (0.000 <0.05). This calculated F-value is much larger than the F-table value of 2.70 at degrees of freedom (df) 3 and 96. It can be concluded that there is a significant simultaneous influence between promotion, influencers, and brand ambassadors on product purchase interest.